Aggregation Bias in the Factor Content of Trade: Evidence from U.S. Manufacturing - Feenstra, Robert C; Hanson, Gordon H (American Economic Review, 2000)
Aggregation Bias in the Factor Content of Trade: Evidence from U.S. Manufacturing by Robert C. Feenstra and Gordon H. Hanson. Published in volume 90, issue 2, pages 155-160 of American Economic Review, May 2000